An All-Solid Dispersion-Compensating Photonic Crystal Fiber Based on Mode Coupling Mechanism in Dual-Concentric Core. (9th December 2020) - Liu, Zhaolun; Zhang, Chunlan; Qu, Yuwei
Abstract : An all-solid dispersion-compensating photonic crystal fiber based on mode coupling mechanism in dual-concentric core has been proposed. The mode coupling characteristics, dispersion, confinement loss of the fiber, and the influence on dispersion of some structure parameters are simulated by full-vector finite element method. By using the relationship between phase matching wavelengths and coupling strength with the change of fiber microstructure parameters, an all-solid dual-concentric-core dispersion-compensating photonic crystal fiber is presented. The structure parameters on dispersion characteristic are investigated. The results demonstrate that the proposed fiber has a large negative dispersion value 8465 ps/(nm·km) at 1550 nm. The effective mode area and the splicing loss to the standard single mode fiber are 12.8  μ m 2 and 1.89 dB at 1550 nm, respectively. At 1550 nm, the confinement loss is less than 1 × 10 −3  dB/km and the bending loss with 2 cm bending diameter is less than 1 × 10 −2  dB/km.